A Numerical Study of Two-Fluid Models with Pressure and Velocity Relaxation (Advances in Applied Mathematics and Mechanics, 2010)
This paper presents a study of pressure and velocity relaxation intwo-phase flow calculations. Several of the present observations have beenmade elsewhere, and the purpose of the paper is to strengthen theseobservations and draw some conclusions. It is numerically demonstrated howa single-pressure two-fluid model is recovered when applying instantaneouspressure relaxation to a two-pressure two-fluid model. Further,instantaneous velocity relaxation yields a drift-flux model. It is alsoshown that the pressure relaxation has the disadvantage of inducing a largeamount of numerical smearing. The comparisons have been conducted by usingnalogous numerical schemes, and a multi-stage centred (MUSTA) scheme fornon-conservative two-fluid models has been applied to and tested on thetwo-pressure two-fluid model. As for others, previously tested two-phaseflow models, the MUSTA schemes have been found to be robust, accurate andnon-oscillatory. However, compared to their Roe reference schemes, theyconsistently have a lower computational efficiency for problems involvingmass transport.